COMPARATIVE RESEARCH REGARDING THE ENERGY EFFICIENCY OF WHEAT CROP, IN ECOLOGICAL AND CONVENTIONAL CULTIVATION SYSTEMS - Mirela PÎRVU (FULGA); Nicoleta OLTENACU; Cătălin-Viorel OLTENACU; Cristiana Silvia BUZATU; Mihai GÂDEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Due to the importance of the winter wheat crop, in ensuring the food needs of the population, and for increasing the average and total production, it is necessary to ensure a high economic efficiency of the use of energy in agriculture, by increasing the degree of mechanization in production processes, the development of irrigations, the substantial increase in the quantities of chemical fertilizers used, the creation of new varieties and hybrids that are more productive and of higher quality, increases direct and indirect energy consumption. In order for this share not to increase, given the substantial growth in agricultural production, it is necessary to apply a complex of measures that ensure, along with the increase in the economic efficiency of energy use, a minimum energy consumption per unit of product or per unit area. Conserving soil and preventing soil degradation has become imperative in our efforts to ensure food security, protect biodiversity and maintain healthy ecosystems. The purpose of establishing this experiment was to compare the results regarding the production achieved in the wheat crop, the expenses incurred, the incomes achieved and the profitability of the crop both in ecological and conventional systems. In the conventional system, the incomes were higher so, the yields were higher. The energy efficiency of the two culture systems analyzed was another aspect studied. For realize one unit of product it was consumed 0.108 kwh in conventional system while, in organic variant it was consumed 0.184 kwh, witch mean a better energetic efficiently for conventional one.